Relationship Patterns of Central and Regional Governments in the Framework of Regional Autonomy: A Study of Regional Independence and Financial Dependence in Sikka District - Didiktus, Oktavianus; Wahda, Wahda; Aswan, Andi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to conduct a study of the regional financial capacity of Sikka Regency within the framework of regional autonomy by referring to an analysis of regional financial independence and dependence. This research is a type of quantitative descriptive research that aims to analyze the regional financial capacity of Sikka Regency based on the concept of regional financial independence and dependence. This research was conducted at the Sikka Regency Regional Government with an observation period from Fiscal Year 2018 to Fiscal Year 2022. The data used in the research was secondary data obtained from the Regional Financial and Asset Management Agency (BPKAD) of Sikka Regency in the form of Budget Realization Report Data. The data analysis technique uses ratio analysis of regional financial independence and dependence. Based on the results of the analysis and discussion, the conclusion that can be outlined is that the financial capacity of the regional government of Sikka Regency is very low with an independence ratio of 11.66% and a regional financial dependency ratio of 78.21%, with an instructive relationship pattern. This provides an understanding that Sikka Regency's regional income comes from transfer funds provided by the central government which is greater than PAD.